Manajemen Infrastruktur Teknologi Informasi: Studi Literature (International Forum of Researchers and Lecturers, 2023)
Management is always interpreted as the process of organizing, regulating, managing human resources, to controlling in order to achieve the objectives of an activity. In everyday life, of course, we cannot avoid management science (POAC). The concept of management is a particular process consisting of planning, organizing, transferring and directing, which is carried out with the help of people and other resources to establish and achieve certain goals. IT infrastructure is a long-term asset which is often referred to as an asset that creates value for an organization. This article thoroughly examines the theory of information technology infrastructure management, by writing this article using the literature research method, it is expected that we can better understand and apply it properly related to information technology infrastructure management.